Vertical jumping performance in young rythmic gymnasts - Kums, T.; Ereline, J.; Gapeyeva, H.; Pääsuke, M. (Biology of Sport, 2005)
Vertical jumping performance characteristics were compared in female rhythmic gymnasts (n=11) and age-matched untrained controls (n=15) aged 12-13 yrs. Maximal squat (SJ), counter-movement (CMJ) and drop jumps from 40 cm height (DJ40), and a modified (30 s) Bosco anaerobic jumping power test were performed on force platform. The results of the sytudy indicated that the Jump heights in SJ, CMJ and DJ40 were greater (p<0.01-0.001) in rhythmic gymnasts than controls. The Jump height in DJ40 was greater (p<0.001) compared with SJ and CMJ only in rhythmic gymnasts. The Jump height ratio CMJ:SJ did not differ in rhythmic gymnasts and controls. The rhythmic gymnasts had greater (p<0.05) jump height ratio DJ:SJ than controls. Mean mechanical power output calculated for every 15 s period of the repeated jumping, and average power output for 30 s repetitive jumping exercise were greater (p<0.01-0.001) in rhythmic gymnasts than controls. The rhythmic gymnasts had higher (p<0.05) fatigue index during repetitive jumping exercise than controls. It was concluded that young elite female rhythmic gymnasts demonstrated a markedly greater ability to use the potentiating effect of stretch-shortening cycle to vertical jumping performance than control subjects during DJ, but not during CMJ. The rhythmic gymnasts produced greater mechanical power during repetitive maximal jumping exercise, but fatigued faster than controls.